PENGEMBANGAN DATABASE PENGELOLAAN SUMBER DAYA AIR UNTUK WILAYAH KABUPATEN PANDEGLANG - Yudo, Satmoko (Center for Environmental Technology, 2014)
In order to support the Government Regulation Number 42 of 2008 on the sustainable management of water resources, it is one of the responsibilities of government and the local government to carry out the management of water resources information system. Kabupaten Pandeglang is one area in Indonesia with the availability of water resources is quite large, so as to support the management of water resources need to built Database Information System for Water Resources Management (SISDA). SISDA is an application program based database created to facilitate the data management of water resources. This program has been applied in the Office Bappeda Pandeglang and information shown include the River Basin Unit (SWS), the Regional Jetting River (DPS), Creeks, Lakes, Swamps, Beaches, Ponds, Dams, Irrigation, Water Monitoring Station, Rain Station, and other information.Ã‚Â Keywords : Water resource of Kabupaten Pandeglang, database, Information System for Water Resources Management.